Dinamika Pondok Pesantren Tremas Pacitan Pasca Masa Fatrah (1952-1965) - Roro Wilis; Wildhan Ichzha Maulana (LP4MK STKIP PGRI Lubuklinggau, 2026)
This research endeavors to analyze the dynamics of the Pesantren Tremas after the fatrah period (the head caregiver vacuum) since the 1948 PKI Madiun revolt. It employs a historical methods, including four stages: heuristics, verification, interpretation, and historiography. Data sources were obtained from oral statements by descendants of Kyai Hamid Dimyathi (the head caregiver of Pesantren Tremas) and relevant textual sources. The results illustrate that Kyai Hamid Dimyathi died as a victim of kidnapping by the PKI group, causing the Pesantren Tremas to enter a fatrah period (1948-1952) and stagnation. During the fatrah period, a deliberation was held by the extended families of Raden Dipomenggolo and Raden Honggowijoyo, who appointed Kyai Hasyim IKyaisan as interim caregiver, assisted by Kyai Darul Kyaioiri and Kyai Nawawi. Next, prepared Kyai Habib Dimyathi and Kyai Harist Dimyathi (Kyai Hamid Dimyathi’s sibling), who was still studying at the time, to become the next head caregiver. After the fatrah period (1952-1965), Kyai Habib Dimyathi and Kyai Harist Dimyathi was appointed as the head caregiver and immediately implemented three programs: renovating the dormitories damaged by the 1948 PKI attack, building a madrasah, and reforming the pesantren’s curriculum.